Induction of Somatic Embryogenesis and Organogenesis in Zimbabwean Sweet Potato (cv Brondal) - Rose T. Masekesa; Edmore Gasura; Gaudencia T. Kujeke; Elizabeth Ngadze; Farisai Chidzwondo (Advances in Agriculture)
Somatic embryogenesis (SE) and organogenesis are crucial in the development of disease free plants and genetic engineering. An investigation was conducted on the ability of treatments containing a combination of 2,4-D and Kinetin to induce either SE or organogenesis from cultured sweet potato cv Brondal leaves. Ten treatments were evaluated and each treatment had an exclusive combination of 2,4-D (at 0.05, 0.1, 0.2, 0.5 or 1 mg/L) to kinetin (at either 0.1 or 0.5 mg/L). Callus initiation occurred earlier in treatments containing higher hormonal concentrations. The 2,4-D to Kinetin ratio had a highly significant (p=0.001) effect on callus growth and proliferation. Increasing 2,4-D to Kinetin ratio promoted profuse explant callusing while increasing Kinetin to 2,4-D ratio suppressed callusing but encouraged organogenesis, in particular shoot production (treatment containing 0.05 mg/L 2,4-D and 0.5 mg/L Kinetin). Embryogenic calli were formed seven weeks after leaf culture in the treatment containing 0.5 mg/L 2,4-D and 0.1 mg/L Kinetin. The embryogenic calli that developed from this treatment emerged from previously nonembryogenic calli. Plantlets produced via the SE pathway proved to be weak and unviable and died within four weeks of germination. In contrast, plantlets produced under organogenesis were strong, grew vigorously, and could be subcultured several times. This disparity may be accounted for by the fact that the cv Brondal embryos that developed under SE were not exposed to an embryo maturation staged before plantlet germination was initiated. The maturation stage would have assisted embryos to reach physiological maturity and a desired level of desiccation, both being critical elements in embryo to plantlet conversion. In this experiment, cv Brondal regeneration from leaf explants was successfully achieved via organogenesis using 0.05 mg/L 2,4-D and 0.5 mg/L Kinetin, and tentative steps towards development of SE based regeneration protocol were established using 0.5 mg/L 2,4-D and 0.1 mg/L Kinetin.